Total serum complement in chickens experimentally infected with infectious bursal disease virus with or without previous vaccination (2003)
Mean titres of serum complement(C') in 100 broiler chicks from day one to week 13 were determined using the complement fixation test. The chicks were assigned to four groups of 25 each namely, unvaccinated unchallenged(UvUc) which served as the controls, vaccinated unchallenged(VUc), unvaccinated challenged (UvC) and vaccinated challenged (VC). The chicks in groups VUc and VC were vaccinated at 3 weeks with locally produced Nigerian fibrogombavac infectious bursal disease virus (IBDV) vaccine. The chicks in groups UvC and VC were challenged at week 6 by intraocular inoculation with virulent IBDV. Complement was first detected at 2 weeks of age in chickens while the highest mean titre was observed at 8 weeks. There was a 4-fold increase in the mean titre of C' in the Uvc group and a 3-fold increase in the VC group. The mean titre of C' was lower on the VUc than those of the control(UvUc). Thus, challenges with IBDV significantly increased serum C' levels in chickens while vaccination caused a decrease. The role of C' in the pathogensis of IBD is dicussed.